A note on generalized harmonic-Cesàro summability - Hiroshi Hiorkawa (International Journal of Mathematics and Mathematical Sciences)
This note shows that conjectures proposed by G. Das and P.C. Mohapatra [1] on inclusion relations between two generalized Harmonic-Cesàro methods of summability, are true.